New Insights into optimal control of nonlinear dynamic econometric models: Application of a heuristic approach - Dmitri Blueschke; Viktoria Blueschke-Nikolaeva; Ivan Savin (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Optimal control of dynamic econometric models has a wide variety of applications including economic policy relevant issues. There are several algorithms extending the basic case of a linear-quadratic optimization and taking nonlinearity and stochastics into account, but being still limited in a variety of ways, e.g., symmetry of the objective function and identical data frequencies of control variables. To overcome these problems, an alternative approach based on heuristics is suggested. To this end, we apply a classical algorithm (OPTCON) and a heuristic approach (Differential Evolution) to three different econometric models and compare their performance. In this paper we consider scenarios of symmetric and asymmetric quadratic objective functions. Results provide a strong support for the heuristic approach encouraging its further application to optimum control problems.
Keywords: C54; C61; E27; E61; E62; 330; differential evolution; dynamic programming; nonlinear optimization; optimal control; Ökonometrisches Modell; Dynamisches Modell; Kontrolltheorie; Nichtlineare Optimierung; Heuristisches Verfahren; Theorie